Analysis Of The Application Of Safety Culture On Motor Sailing Vessels In Supporting Shipping Safety - Rosnani Rosnani (International Journal of Marine Engineering Innovation and Research, 2023)
Paotere Port is port that plays an important role in the delivery of basic needs to various islands in South Sulawesi. The problems faced by Paotere related to safety aspects include the lack of understanding of safety by the ship and the lack of socialization about safety and applicable rules so that a joint commitment is needed, both regulators, operators and service users to make safety a culture and necessity. The purpose of this study was to determine the application of safety culture by the crew of the shipping vessels in Paotere port in terms of situational and behavioral aspects.The type of research is descriptive quantitative with data collection methods of observation, interviews and questionnaires. Data analysis technique used was descriptive quantitative by using frequency and percentage table distributions to reveal knowledge/understanding of ship crews on safety culture. The results obtained were that the implementation of the situational aspect of safety culture has not been fully implemented, safety equipment and equipment are still lacking and unsuitable for use, from the behavioral aspect the description of the crew's safety culture regarding life safety equipment, work safety and safety signs on board is included in the category still lacking, as well as the lack of safety socialization to ship owners, public shipping companies and ship crews